Assessment of Carotid Plaque Stability Using Contrast-Enhanced Ultrasound and Its Correlation With the Expression of CD147 and MMP-9 in the Plaque - Huang, Shanshan; Wu, Xinyin; Zhang, Linlin; Wu, Jianming; He, Yi; Lai, Manlin; Xu, Jiaqi; Li, Zhenzhou (Frontiers in Computational Neuroscience, 2021)
To investigate the correlation between the enhancement degree of Contrast-enhanced ultrasound (CEUS) and the expression of CD147 and MMP-9 in carotid atherosclerotic plaques in patients with carotid endarterectomy, and to evaluate the diagnostic efficacy of CEUS using pathological results as gold standard. Thirty-eight patients who underwent carotid endarterectomy for carotid stenosis in the Department of Neurovascular Surgery of the Second People's Hospital of Shenzhen from July 2019 to June 2020 were selected. Preoperatively, two-dimensional ultrasound was applied to all patients to assess the characteristics of the plaque and the degree of stenosis, and CEUS was used to evaluate the surface morphology of the plaque and the distribution of neovascularization. Postoperatively, pathological sections and immunohistochemical analysis of CD147 and MMP-9 levels in the plaque were performed on the stripped plaque tissue. Among the 38 patients, pathological results showed that 10 cases were in the stable plaque group and 28 cases were in the vulnerable plaque group. There were more smokers in the vulnerable plaque group, with higher intra-plaque CD147 and MMP-9. The difference of ultrasound plaque surface morphology grading and contrast grading between the two groups was statistically significant. CD147 was higher in the CEUS grade IV group than in the grade I group (P=0.040) and the grade II group (P=0.010). MMP-9 was higher in the CEUS grade IV and grade III group than in the grade II group (P=0.017, P=0.015 respectively); Intraplaque contrast enhancement intensity was positively correlated with CD147 levels (r=0.462, P=0.003) and MMP-9 levels (r=0.382, P=0.018). There was a strong consistency between the assessment of plaque vulnerability by CEUS and by histopathological HE (Kappa = 0.671, P < 0.01). CEUS had a sensitivity of 89.2%, a specificity of 80.0%, a positive predictive value of 92.6%, a negative predictive value of 72.7% and an accuracy of 86.8% for the diagnosis of vulnerable plaques. CEUS is a reliable, noninvasive test for evaluating vulnerable plaques with a highly consistency with pathological findings. The higher the degree of intraplaque enhancement, the higher the level of CD167 and MMP-3 in the tissue.